New host-plants records of Afrotropical Gelechiidae (Lepidoptera), with description of three new species - Bidzilya, Oleksiy (Zootaxa, 2021)
First and additional host-plant records for 38 species of Gelechiidae from South Africa and Kenya are presented. An annotated list with brief descriptions of larval biology and known geographical distributions is presented. Three species are described as new: Mesophleps kruegeri sp. nov. (Namibia: Kavango Region and South Africa: Limpopo Province), Istrianis inquilinus sp. nov. (South Africa: North West Province), and Teleiopsis sharporum sp. nov. (South Africa: Limpopo Province). The new combination Istrianis epacria (Bradley, 1965) comb. nov. is proposed. The male genitalia of Hypatima melanecta (Meyrick, 1914) is described for the first time. It is noticed that male hitherto associated with T. commaculata (Meyrick, 1918) in fact refers to T. pundamilia Bidzilya & Mey, 2018. Hypatima stasimodes (Meyrick, 1931), Dichomeris coenulenta (Meyrick, 1927), Dichomeris eustacta Meyrick, 1921, Neotelphusa similella Janse, 1958 and Argophara epaxia Janse, 1963 are recorded for the first time from South Africa, and Istrianis epacria is new for Kenya. The adults, male and female genitalia are illustrated for some species mentioned in paper. The first record of the genus Teleiopsis Sattler, 1960 from South Africa is briefly discussed.